2016
DOI: 10.1007/s11746-016-2910-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Antioxidative Kinetics of Hydroxytyrosol in Selected Lipid Systems of Different Unsaturation Degree

Abstract: The oxidation kinetics of the purified triacylglycerols of olive, canola, and fish oils as affected by different concentrations of hydroxytyrosol were studied at 60–100 °C. On average, hydroxytyrosol improved the temperature susceptibility (temperature coefficient, TC, and Q10 number) of olive oil, whereas opposite results were observed for canola and fish oils. Despite the results observed in canola and fish oils, hydroxytyrosol caused much greater changes in the Arrhenius equation parameters (activation ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 20 publications
9
28
1
Order By: Relevance
“…Previous studies also showed that minor changes in the E a can result in significant changes in the Z . Similar to T c and Q 10 , the E a and Z were affected more by the 1% and 0.1% pomegranate peel and pomegranate seeds, compared to their concentrations of 0.01%. Meanwhile, pomegranate peel (1%) was more effective than pomegranate seed (1%).…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Previous studies also showed that minor changes in the E a can result in significant changes in the Z . Similar to T c and Q 10 , the E a and Z were affected more by the 1% and 0.1% pomegranate peel and pomegranate seeds, compared to their concentrations of 0.01%. Meanwhile, pomegranate peel (1%) was more effective than pomegranate seed (1%).…”
Section: Resultsmentioning
confidence: 68%
“…The lipid oxidation rate is partly defined by the concentration and dissociation rate of the activated complex. The values of Δ S ++ and Δ H ++ are considered as the level of disorder and the thermal energy required for the steric changes of the activated reactant molecules, respectively …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Gibbs free energy of activation, Δ G ‡ , was obtained by eqn , with the results shown in Table S4. The higher the Δ G ‡ , the lower the reaction rate (Mahdavianmehr et al ., ; Garvin et al ., ). The Δ G ‡ values supported the conclusions drawn from Δ H ‡ and Δ S ‡ : HHE formation occurred more readily in LO than in RO, as indicated by the lower Δ G ‡ values in LO.…”
Section: Resultsmentioning
confidence: 99%
“…The formation and dissociation rate of the activated complex is affected by the enthalpy of activation (DH ‡ ) and entropy of activation (DS ‡ ). The values of DH ‡ and DS ‡ represent the thermal energy required for steric changes and the level of disorder, respectively, of the activated reactant molecules (Mahdavianmehr et al, 2016). The more positive DH ‡ is, the more endothermic the formation of the activated complex is.…”
Section: Activated Complex Theory Parametersmentioning
confidence: 99%